CHEMICAL EVALUATION AND YIELD ESTIMATE OF ALLUVIAL SEDIMENTS OF FIVE MAJOR RIVERS IN SOUTHWESTERN NIGERIA FOR GLASS RAW MATERIALS - Ibrahim, Adesoji A.; Jolly, B. A.; Ochepo, J. (FUDMA JOURNAL OF SCIENCES, 2025)
Alluvial sands are detrital materials which are transported by a river and deposited, usually temporarily, at points along the flood plain of the river. These sands are majorly consumed in construction industries, especially in developing countries like Nigeria. However, with value addition, it could have a high value-to-mass ratio. The alluvial sands of five major rivers in southwestern Nigeria were investigated. A total of 51 samples were collected along the channels of River Yewa, River Ogun, River Ona, River Osun, and River Shasha during the dry season in 2024. The objectives were to: assess the major chemical composition of alluvial sand vis-à-vis specification requirements for various glass industries; determine the beneficiation requirements where necessary for the silica sand to meet specification; and determine the tonnage of sediments and silica yields per year. The samples were analysed using (XRF) and XRD. The mean percentage of major oxides for the five rivers are SiO2 75.78%, TiO2 1.97%, Al2O3 8.96%, Fe2O3 4.45%, MnO 0.27%, MgO 1.25%, CaO 2.49%, Na2O 0.08%, P2O5 0.52%, Cr2O3 0.23%, and LOI 9.79%. Based on the chemical specification, it was found that the sands are not suitable for the production of first-quality glass materials. However, they are suitable for glass wool, optical glass, flat glass, glass ceramic, container glass etc. based on Best Available Techniques BAT, (2013). The Chemical Index of Alteration (CIA) was adopted to estimate the sediment yield of all the rivers. The average sediment yield of all the rivers was estimated at 2772.64t/km2/yr. Out of which...
Keywords: Silica sand; Weathering; Specification; Beneficiation; CIA